Places rated almanac : the classic guide for finding your best places to live in America - Savageau, David (Places Rated Books, 2007)
Rates the 379 metropolitan areas in the United States according to nine factors such as housing, transportation, health care, and recreation, to aid people in deciding where and if to relocate to a new city.